Physicochemical Properties, Oxidative Stability, and Sensory Quality of Lamb Sausage Added with Green Tea Leaves (Camelia sinensis) Powder - L. Purnamayanti; Jamhari Jamhari; C. Hanim; A. Irawan (Faculty of Animal Science, Bogor Agricultural University, 2020)
Green tea leaves as a source of natural antioxidants has a huge potential to improve sausage quality from lamb meat, in line with an increase of people concern in functional food products. This study aimed to evaluate inclusion of green tea leaves (Camelia sinensis) powder (GTP) into lamb sausage on physicochemical properties, total microbes, oxidative stability, and sensory quality. Three lambs aged one year was slaughtered as sausage meat source. Incorporation of 0.0%, 1.0%, 1.5%, and 2.0% GTP to lamb sausage during 0, 7, and 14 days of storage was conducted in a completely randomized design of ANOVA with five replications in each treatment. Few changes were observed on chemical and physical qualities by adding 1% GTP, particularly on protein and water holding capacity (WHC) (p<0.05), while moisture, fat, pH, and tenderness were not affected (p>0.05). Lipid oxidation and the number of total plate count (TPC) were reduced by 36%-40% and 31%-49%, respectively by the inclusion of 1% GTP during storage time (p<0.05). Adding GTP negatively affected the sensory quality of lamb sausage since the score of acceptability reduced in the group of sausages contained GTP although the scores for color, flavor, and odor were higher with GTP addition. The incorporation of GTP was effectively inhibiting bacterial growth and lipid oxidation in the lamb sausage. However, GTP was also ineffective at improving the sensory quality of the sausage.